2008
DOI: 10.1002/hep.22175
|View full text |Cite
|
Sign up to set email alerts
|

Activation of liver X receptor sensitizes mice to gallbladder cholesterol crystallization†

Abstract: Gallstone disease is a hepatobiliary disorder due to biochemical imbalances in the gallbladder bile. In this report, we show that activation of nuclear receptor liver X receptor (LXR) sensitized mice to lithogenic diet-induced gallbladder cholesterol crystallization, which was associated with dysregulation of several hepatic transporters that efflux cholesterol, phospholipids, and bile salts. The combined effect of increased biliary concentrations of cholesterol and phospholipids and decreased biliary concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 50 publications
1
41
1
1
Order By: Relevance
“…This LXR␣ autoregulation seemed to be species specific because it was observed only in human cell lines but not in murine cells. Although LXR␣ has many beneficial function, overexpression and/or activation of LXR␣ can be harmful in certain tissue and cellular context, such as the lipogenic side effect in the liver (4,5) and sensitization of mice to cholesterol gallstone disease (9). As such, it is interesting to know whether there is a negative regulatory pathway that can function as checks and balances to maintain a proper concentration of LXR␣.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This LXR␣ autoregulation seemed to be species specific because it was observed only in human cell lines but not in murine cells. Although LXR␣ has many beneficial function, overexpression and/or activation of LXR␣ can be harmful in certain tissue and cellular context, such as the lipogenic side effect in the liver (4,5) and sensitization of mice to cholesterol gallstone disease (9). As such, it is interesting to know whether there is a negative regulatory pathway that can function as checks and balances to maintain a proper concentration of LXR␣.…”
mentioning
confidence: 99%
“…After ligand binding, LXR forms a heterodimer with the retinoid X receptor (RXR) that binds to LXR response elements (LXREs) in the promoters of LXR target genes. LXRs exhibit effects on diverse physiological functions, ranging from cholesterol (3) and lipid metabolism (4,5) to antiinflammation (6,7), hepatobiliary diseases (8,9), and steroid hormone biosynthesis and metabolism (10,11).…”
mentioning
confidence: 99%
“…SULT2A1 catalyzes the sulfonation of a wide range of endogenous and exogenous compounds that have diverse effects on various physiologic functions Schultz et al, 2000;Repa and Mangelsdorf, 2002;Joseph et al, 2004;Cummins et al, 2006;Zelcer and Tontonoz, 2006;Gong et al, 2007;Uppal et al, 2007Uppal et al, , 2008. As a highly inducible phase II conjugating enzyme, the transcriptional effect of nuclear receptors on SULT2A1 gene expression and the physiologic implication of this regulation have drawn extensive interest.…”
Section: Discussionmentioning
confidence: 99%
“…Through its gene regulatory activities, LXR is involved in diverse physiologic functions in rodents, including cholesterol and lipid metabolism Schultz et al, 2000;Repa and Mangelsdorf, 2002), anti-inflammation (Joseph et al, 2004;Zelcer and Tontonoz, 2006), hepatobiliary disease (Uppal et al, , 2008, acetaminophen liver toxicity (Saini et al, 2011), and steroid hormone biosynthesis and metabolism (Cummins et al, 2006;Gong et al, 2007;Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been demonstrated in vivo in mice that activation of LXRs prevents bile acid toxicity and cholestasis in female mice, which is associated with an increased expression of bile acid-detoxifying genes and a regulation of certain bile acid transporters [46]. Nevertheless, and despite this favourable effect of LXR, very recently, it has been shown that activation of LXR promotes cholesterol crystallisation [47]. This lithogenic effect of LXR is associated with dysregulation of hepatic transporters resulting in a combined effect of increased biliary concentrations of cholesterol and phospholipids and decreased biliary concentrations of bile salts, leading therefore to an increased cholesterol saturation index.…”
Section: Lxrs and Bile Acid Metabolismmentioning
confidence: 99%